PERENCANAAN TENAGA KERJA DI PT GLORY PACKINDO - Susanti, Christine; Handes, Dicky; Effany, Efanny; Wajong, Andre M. R. (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
The main problem experienced by PT. Packindo Glory is less optimal manpower planning in the company. Hence, the company often could not meet the demand of cardboard order. Therefore, this study is structured to assist the company in addressing this problem. In the planning of manpower requirement, we proposed and analyzed options of adding extra manpower and overtime working hours. The analysis are supported by data of requested carton during 32 weeks, data of regular working hours, and data of overtime hours and labor cost. The demand data are used to estimate the need for 16 weeks. The methodology used for forecasting the demand is the linear regression method, the Double Exponential Smoothing (DES) parameter Brown, and DES parameter Holt. The results show that the smallest error is found on the regression methods. Therefore, it will be used in estimating the carton demand. Based on demand data, we compile query plan requirements. The results show that the right strategy for the company for 16 weeks period ahead is by increasing the working hours of the overtime, which will further lower the cost by Rp. 640.000 or 11.11% cost reduction compared to reduction by adding workers. Based on the limited hours of overtime work available, then after 44 hours of overtime work, the company still needs to increase the workforce to meet the demand for paperboard.